System Of Testing And Grouping Of Student Development In Pure Interest Paud With Methodk-Means Clustering - Anisya Sonita; Yovi Apridiansyah; Muhammad Husni Rifqo; Rahmat Pariza (Jurnal Komputer, Informasi dan Teknologi, 2022)
The Bunga Murni PAUD in Bengkulu City, precisely in Sumber Jaya, is one of the facilities for kindergarten education. Where the school will be a place for children to improve themselves from various aspects of child development. Bunga Murni PAUD has not been able to carry out testing the development of their students by means of the Screening Method, because it will require a lot of money and time to carry out these activities, starting from preparing the child development form data that must be printed and then collecting the parents of students to come to the school. PAUD to fill out the form which is considered quite time consuming and sometimes has to be hindered because some parents cannot attend. Seeing from these problems, therefore in this study a website-based system will be created that will assist in these activities. In this system, a process for filling out child development forms will be made as well as a process for grouping child development. To see the results of grouping children's development based on the completed child development form, it will be made using the K-Means Clustering method to find out which children fall into the category of active child development and less active child development. The results of the tests in this study showed that from the 10 samples of students tested, 5 students entered the category of active child development and 5 students entered the less active child development category.